The differential effects of cooking methods on the nutritional properties and quality attributes of meat from various animal sources - Olagunju, Aderonke Ibidunni (Array, 2020)
This study investigated the various effects of two food product processing methods (boiling and grilling) on the nutritional composition (fatty acid, amino acid profiles) of meat from cows, goats, and rabbits. Freshly slaughtered animals were cleaned and subjected to boiling and grilling. Cooking loss varied with cooking methods; grilling resulted in the highest cooking loss, especially in cow meat (52.95%). Data from the proximate composition analysis revealed that both raw and grilled meat samples of rabbit meat contained the highest amount of protein (22.93 and 22.20 %, respectively) when compared to the corresponding samples from the other two animal sources. Additionally, rabbit meat contained a low level of fat (1.85%), which was not significantly different than the boiled samples (1.75, 1.76 %). Boiling and grilling significantly increased the in vitro protein digestibility of meat. The meat showed significant sources of both essential and non-essential amino acids. Rabbit meat showed a higher proportion of essential amino acids and a higher protein efficiency ratio. Boiled goat meat had a lower proportion of saturated fatty acids (SFA), boiled meat had higher polyunsaturated fatty acids (PUFA) than its grilled counterpart. Goat meat showed a favourable fatty acid profile. Thus, goat and rabbit meat are healthier alternatives to beef, and both boiling and grilling are useful in maintaining the nutritional qualities of meat.